PENGARUH INSENTIF TERHADAP SEMANGAT KERJA KARYAWAN PABRIK CRUDE PALM OIL (Kasus Bagian Produksi PT. Tunggal Yunus Estate Kabupaten Kampar) - Anita "; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted at PT. Tunggal Yunus Estate Kampar district. This study aimed to determine the effect of incentives on employee morale in the production of PT. Tunggal Yunus Estate Kampar district. Incentives as an independent variable ( X ) and morale as the dependent variable (Y) . This study took a number of respondents as many as 63 people . Data obtained through questionnaires were then tested further processed through a statistical analysis as a simple linear regression analysis, t test, correlation analysis and determination with the help of SPSS .The results of this study indicate that the results of hypothesis testing t test , t (8,479) > t table (1,670). This suggests that the incentive effect on employee morale. The amount of the incentive effect on the morale of the production employees of PT. Tunggal Yunus Estate amounted to 54.1 % .Keywords : Human Resource Management , Incentive , Morale .